Argamassa de assentamento em blocos de concreto para alvenaria estrutural estudo de desempenho - Natalia Souza Diniz Alves (2018)
The present study proposes to find the mortar that promotes the best performance in a structural masonry of concrete blocks. It was compared industrialized mortars, mortars dosed on site without additive and mortars dosed on site with additives. Tests were performed in fresh and hardened state (standardized and nonstandardized). For the adherence analysis the existing standards did not predict the pullout situation according to the efforts in the structural masonry, making it impossible to evaluate. The potential adherence test was adapted and a test for shear strength was created. In addition, considering that this is study with a practical application, the normative parameters limiting the mechanical strength tests (compression) for mortars were verified, which, in the case of the blocks tested, is 8,3 MPa. Thus it was realized that the dosages on site 1:0,5:6 and 1:0,5:9 with and without additives were not applicable for the tested blocks. The evaluation of the mortars, with compressive strength lower than the limit imposed by the standard, by the graph scale method, the one that obtained the best performance was the mortar measured on site without plasticizer additive with 1:0,5:9 dosage for use in structural masonry composed of concrete blocks with estimated compressive strength (in relation to the net area) of 9,9MPa